Development and validation of a HPLC method for the simultaneous estimation of amlodipin and telmisartan in pharmaceutical dosage form - Sinha S.K.; Shrivastava P.K.; Shrivastava S.K. (My University, 2025)
Objective: To develope and validate a simple and rapid isocratic reversed-phase highperformance liquid chromatographic method (RP-HPLC) for the simultaneous estimation of amlodipin and telmisartan in combined dosage form. Methods: The chromatographic separation was achieved by using mobile phase acetonitrile and 0.05M sodium dihydrogen phosphate buffer (60:40) adjusted to pH 6.0, a C-18 column, perfectsil target ODS3 (150 mm × 4.6 mm i.d., 5 μm). The mobile phase was pumped at a flow rate of 0.8 mL/min and the eluents were monitered at 254 nm. Results: Retention times were 4.0 min and 8.2 min for amlodipine and telmisartan respectively. The method was validated in terms of accuracy, precision, linearity, range, specificity, limit of detection and limit of quantitation. Linearity for amlodipine besylate and telmisartan was established in the range of 5-30 and 10-60 μg/mL, respectively. The recoveries for the two compounds were above 96%. Conclusions: This method was found to be efficient, accurate, precise, specific and economic and is suitable for routine quality control analyses. © 2012 Asian Pacific Tropical Biomedical Magazine.